- Move 4y to the front so it should be 4y=12-3x
- Divide the equation like how I did in the picture above then you should have y=3-3/4x
- Then you switch it to y=-3/4x+3 and that's your answer.
Now for 6x+2y=6
- Move 2y to the front so it looks like 2y=6-6x
- Then you divide the equation by 2 like in the photo above and that should give you y=3-3x
- Finally you switch the equation to y=-3x+3 because we are using the Slope Intercept Form. (Y=mx+b). That's your answer.
Sorry if my handwriting is bad.